Response of the Bight of Benin (Gulf of Guinea, West Africa) coastline to anthropogenic and natural forcing, Part1: Wave climate variability and impacts on the longshore sediment transport. (1st November 2015) - Almar, R.; Kestenare, E.; Reyns, J.; Jouanno, J.; Anthony, E.J.; Laibi, R.; Hemer, M.; Du Penhoat, Y.; Ranasinghe, R.
Abstract: The short, medium and long-term evolution of the sandy coastline of the Bight of Benin in the Gulf of Guinea, West Africa, has become a major regional focal point due to the rapid socio-economic development that is occurring in the region, including rapid urbanization and a sharp increase in harbor-based trade. Harbors have a significant impact on the present evolution of this coast, notably by affecting longshore sediment transport. However, little is known of the environmental drivers, notably the wave climate, that governs longshore sediment transport and the ensuing pattern of shoreline evolution of this coastal zone. This article aims to address this important knowledge gap by providing a general overview of coastal evolution in the Bight of Benin and the physical processes that control this evolution. Here, the 1979–2012 ERA-Interim hindcast is used to understand the temporal dynamics of longshore sediment transport. Oblique waves (annual average H s =1.36 m, T p =9.6 s, S-SW incidence) drive an eastward drift of approximately 500, 000 m 3 /yr. The waves driving this large longshore transport can be separated into two components with distinct origins and behavior: wind waves generated locally in the Gulf of Guinea and swell waves generated in the southern hemisphere sub- (30–35°S), and extra-tropics (45–60°S). The analysis undertaken here shows that the contribution to the gross annual longshore transport from swell wave-driven longshore currents is an order of magnitude larger than the local wind wave-driven longshore currents. Swell waves are dominantly generated by westerlies in the 40–60°S zone and to a lesser extent by trade winds at 30–35°S. The longshore sediment drift decay (−5% over 1979–2012) is found to be linked with a decrease in the intensity of westerly winds associated with their southward shift, in addition to a strengthening of the trade winds, which reduces the eastward sediment transport potential. The equatorial fluctuation of the Inter-Tropical Convergence Zone (ITCZ) is found to explain most of the variability in transport induced by wind waves, while the Southern Annular Mode (SAM), an extra-tropical mode, has a predominant influence on transport induced by swell waves. The ITCZ and SAM have, respectively, a negative and positive trend over the period 1979–2012 that explains the decrease in both wind- and swell-wave-induced transport. For future scenarii, General Circulation Models (GCMs) predict a stabilization of the SAM, and, thus, a non-substantial or weak change in longshore sediment transport can be expected on the coast of the Bight of Benin. Highlights: Multi-scale study of the LST from present and future metocean datasets. Swell-wave LST linked to SAM, wind-wave LST to ITCZ. LST decreasing trend unlikely to continue in future from SAM stabilization.